REGENERACIÓN in vitro DE PLANTAS DE “aguaymanto” (Physalis peruviana L.) MEDIANTE EL CULTIVO DE HIPOCÓTILOS Y COTILEDONES UTILIZANDO 6-BENCILAMINOPURINA (BAP) Y ÁCIDO 2,4-DICLOROFENOXIACÉTICO (2,4-D) - HERNANDEZ VILLALOBOS, Karla Violeta (2019)
Physalis peruviana L. “goldenberry” is a solanaceous that because of its high nutritional value and medicinal properties has been gained great importance in countries such as Ecuador, Colombia and Peru. This cultivation presents high variability owing to their main method of propagation involves the use of seeds. Therefore, is necessary to develop a protocol that allows its mass production maintaining homogeneous characteristics. In this sense, the objective of this research was regenerate plants from in vitro cultures of hypocotyls and cotyledons of P. peruviana using different concentrations of 2,4-D (0.25, 0.5 y 1.0 mg/L) and BAP (0.1, 0.25 y 1.0 mg/L). Callus formation was induced in all treatments in both hypocotyls and cotyledons, obtaining up to 100% of callogenesis in T4 (0.25 mg / L of 2,4-D + 0.1 mg / L of BAP). Root induction was obtained in treatments T7, T8 and T9 using hypocotyl explants, T7 (0.1 mg / L of 2,4-D + 1.0 mg / L of BAP) was the treatment with the highest number of induced roots per explant (1.4) and greatest root length (0.3 cm.); whereas, in the cotyledons, roots were induced in treatments T1, T4, T7, T8 and T9, being T8 (0.5 mg / L of 2,4-D + 1.0 mg / L of BAP) and T9 (1 mg / L of 2,4-D + 1.0 mg / L of BAP) the most effective treatments with 16.3 and 16.5 roots per explant and 4.36 and 5.13 centimeters of root length, respectively. It was possible to induce 16.67% of shoots when applying the T9 treatment in cotyledons.